Strategic Transparency and Administrative System Reform A Case Study at the University of Kufa - Hamd Kareem Al-Hdrawy; Saeed Ali Ghafl; Hussein Mohammed Ali (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
This study aims to identify the relationship between strategic transparency and the administrative reform. This study adopted the subject of the environment of strategic transparency as an explanatory variable and the administrative reform and its requirements as a dependent variable, A structural model was built and tested, Based on the results, conclusions were reached, the most important of which is that the adoption of organizational change and the clarity of modern labor rules and ensuring no waste, contributes to improve the performance indicators that required for reform process.